The development of novel solid phase methodologies for the synthesis of atypical peptides and non-peptide entities - Kellam, Barrie (1996)
Solid phase peptide synthesis (SPPS) of branched/cyclic peptides, multiple antigenic peptides (MAPs), pseudopeptide toxins etc. requires amine protection orthogonal to the established Fmoc/Boc protocols. It was envisaged that progression from Dde to N-1-(4-Nitro-l,3-dioxoindan-2-ylidene)ethyl (Nde) amino acid protection would maintain the stipulated orthogonality, whilst improving the hydrazine mediated deprotection. A selection of Nα-Nde-amino acids were efficiently synthesised and their compatibility with SPPS conditions demonstrated by the synthesis of a number of peptides. The Nde group displayed a faster and more easily monitored deprotection profile and similar orthogonality when compared with the Dde group. The selective primary amine protecting characteristics of the Nde group was illustrated by the synthesis of N¹N⁸-bis Nde-spermidine which was subsequently utilised in the solid phase synthesis of the natural product, dihydrotrypanothione.